2006
DOI: 10.1101/gad.1397406
|View full text |Cite
|
Sign up to set email alerts
|

Functional coupling of RNAP II transcription to spliceosome assembly

Abstract: The pathway of gene expression in higher eukaryotes involves a highly complex network of physical and functional interactions among the different machines involved in each step of the pathway. Here we established an efficient in vitro system to determine how RNA polymerase II (RNAP II) transcription is functionally coupled to pre-mRNA splicing. Strikingly, our data show that nascent premessenger RNA (pre-mRNA) synthesized by RNAP II is immediately and quantitatively directed into the spliceosome assembly pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 71 publications
(79 reference statements)
7
120
0
1
Order By: Relevance
“…Here, splicing and degradation of intronic RNA occur co-transcriptionally, with degradation of intronic RNA beginning even before the polymerase reaches the next exon, and well before it terminates. These results contrast with a genome-wide analysis that indicates that premRNA splicing in yeast is predominantly posttranscriptional (26); but the results are consistent with observations pointing to a functional coupling between transcription and splicing (27,28).…”
Section: Discussionsupporting
confidence: 67%
“…Here, splicing and degradation of intronic RNA occur co-transcriptionally, with degradation of intronic RNA beginning even before the polymerase reaches the next exon, and well before it terminates. These results contrast with a genome-wide analysis that indicates that premRNA splicing in yeast is predominantly posttranscriptional (26); but the results are consistent with observations pointing to a functional coupling between transcription and splicing (27,28).…”
Section: Discussionsupporting
confidence: 67%
“…Functional coupling has also been inferred in experiments of Das et al (2006). These authors reported an apparent improvement in the kinetic parameters of splicing, of RNAP II-synthesized transcripts, and rapid formation of a splicing-and RNAP II-specific high MW complex.…”
Section: Discussionmentioning
confidence: 88%
“…In the past few years successful attempts were made to develop systems that coupled transcription and capping (Moteki and Price 2002), as well as transcription and polyadenylation (Adamson et al 2005;Rigo et al 2005). In vitro systems that combine transcription and splicing have also been described (Ghosh and GarciaBlanco 2000;Ibrahim et al 2005;Das et al 2006). However, while both transcription and splicing were shown to take place in these studies, it is unclear whether there was a functional coupling between the two processes, that is, whether the properties of the splicing reaction were affected in a significant way by transcription.…”
Section: Resultsmentioning
confidence: 99%
“…RNA was extracted from the supernatant (cytoplasmic fraction) and the nuclei pellet using guanidinium-based extraction protocols. Validation of the efficiency of nuclear/cytoplasmic partitioning was performed by quantifying levels of unspliced, pre-mRNAs (see below for primer sequences), which are known to be highly enriched in the nucleus due to their short half-life (20).…”
Section: Methodsmentioning
confidence: 99%